Pilot Metal Workload in Flight Operation: A case study of Indonesian Civilian Pilot - Abadi Dwi Saputra (Aceh International Journal of Science and Technology)
This type of activity or work with high stress level and requires more concentration and attention, in this case is the aircraft operation. Thereby mental workload is the most dominant than the physical workload. And this is what should have been a concern, because if mental workload endured by pilot is excessive, it will lower down the quality of work and lead to work safety;  in this case the aircraft operation. Subjective Workload Assessment Technique (SWAT) method is used to measure mental workload value, this method consists of three dimensions with their levels, there are: time, mental effort, and psychological stress load. The aim of this study was to know the mental workload of the pilot of an aircraft in flight dimensions: phases of time, phase of flight, terrain condition, and weather, and identifies what factors the most dominant for build of mental workload. The results of studies showed that pilot mental workload will increase when a pilot faced with flight conditions do at early morning (00.00-05:59 am), during weekend and enters the peak season period, and the aircraft will be landing procedures, and also in case of change of wind conditions in flight, and will increasingly when pilot exposed to aircraft operating with route condition which has a land surface is mountainious. This study also showed that the time dimension factor (T) significantly affects the mental workload of pilots, indicating that they put more emphasis on this factor when they are considering workloads.